Regulation of Cyclin A-Cdk2 by SCF Component Skp1 and F-Box Protein Skp2 - Yam, Cain H. (American Society for Microbiology, 1999)
Cyclin A-Cdk2 complexes bind to Skp1 and Skp2 during S phase, but the function of Skp1 and Skp2 is unclear. Skp1, together with F-box proteins like Skp2, are part of ubiquitin-ligase E3 complexes that target many cell cycle regulators for ubiquitination-mediated proteolysis. In this study, we investigated the potential regulation of cyclin A-Cdk2 activity by Skp1 and Skp2. We found that Skp2 can inhibit the kinase activity of cyclin A-Cdk2 in vitro, both by direct inhibition of cyclin A-Cdk2 and by inhibition of the activation of Cdk2 by cyclin-dependent kinase (CDK)-activating kinase phosphorylation. Only the kinase activity of Cdk2, not of that of Cdc2 or Cdk5, is reduced by Skp2. Skp2 is phosphorylated by cyclin A-Cdk2 on residue Ser76, but nonphosphorylatable mutants of Skp2 can still inhibit the kinase activity of cyclin A-Cdk2 toward histone H1. The F box of Skp2 is required for binding to Skp1, and both the N-terminal and C-terminal regions of Skp2 are involved in binding to cyclin A-Cdk2. Furthermore, Skp2 and the CDK inhibitor p21(Cip1/WAF1) bind to cyclin A-Cdk2 in a mutually exclusive manner. Overexpression of Skp2, but not Skp1, in mammalian cells causes a G(1)/S cell cycle arrest.